2014
DOI: 10.5812/ircmj.14839
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Postpartum Maternal Mental Health With Breastfeeding Status of Mothers: A Case-Control Study

Abstract: Background:Maternal health status might have an important effect on breastfeeding, growth, and general health of the infants.Objectives:This study was conducted to assess the association between maternal mental health and breastfeeding status of mothers in Kashan province.Patients and Methods:This case-control study was conducted on 458 mothers in two groups of unsuccessful breastfeeding (case) and successful breastfeeding (control) attending Kashan province health clinics. In this study, the GHQ questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 19 publications
2
16
0
5
Order By: Relevance
“…Our results consistent to another local study (2014) which showed 65.8% of Iranian mothers had breastfeeding in 4 first months but this rate decreased to 24 months [2]. Spears and Garbarino in their studies also revealed that the prevalence rate of the breastfeeding initiation rate was much more than breast feeding sustaining after 6 months or latter [17] [18].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Our results consistent to another local study (2014) which showed 65.8% of Iranian mothers had breastfeeding in 4 first months but this rate decreased to 24 months [2]. Spears and Garbarino in their studies also revealed that the prevalence rate of the breastfeeding initiation rate was much more than breast feeding sustaining after 6 months or latter [17] [18].…”
Section: Discussionsupporting
confidence: 81%
“…It is a source of protein, lipid, oligosaccharide, vitamins, elements, hormones, enzymes, growth and immune factors that can adjust over time based on infant's need [1]. Breastfeeding protects children against respiratory tract infections, atopic dermatitis, asthma, type II diabetes, obesity, and sudden infant death syndrome [2]. Suboptimal breastfeeding is responsible for children death (under 5 years old) due to infections (45%), diarrhea (30%) and acute respiratory disease (18%) [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Moreover, breastfeeding can help to build up a strong bond between the mother and her child, which may help to establish normal or positive feelings and emotions in both mother and child to prevent post-partum depression. 9 …”
Section: Introductionmentioning
confidence: 99%
“…Optimal outcome is reported from mothers with exclusive breastfeeding (8). According to studies in countries outside of Iran, only slightly more than half of mothers would continue to exclusively breastfeed their infants until four months of age (9). A number of factors can lead to early cessation of breastfeeding.…”
Section: Introductionmentioning
confidence: 99%